MEDIASTINAL TUBERCULOSIS PRESENTING WITH STERNAL OSTEOMYELITIS AND DISCHARGING SINUS - Gondal, Ghulam Murtaza; Mushtaq, Sumera; Masood, Rehan; Hussain, Tassawar; Ghafoor, Adnan; Majeed, Dawar (Journal of Postgraduate Medical Institute, 2011)
Tuberculosis even in countries where tuberculosis is endemic like Pakistan. Frank presentation as discharging sinus is even more uncommon. We describe a case where a patient presented with constitutional symptoms of fever, loss of appetite, significant weight loss and an erythematous tender lesion over the sternum with a discharging sinus without any features of pulmonary tuberculosis. The case was initially not diagnosed by routine laboratory tests and the lesion was just considered as a boil until presented to tertiary care hospital as discharging sinus. Plain Radiographs showed lytic lesion on the inner aspect of sternum and histopathology of the aspirate from the lesion confirmed the presence of epithelioid granulomas and acid fast bacilli on staining. Patient responded very well to 12 months of antituberculosis treatment.